Measuring the diversification of energy sources: The energy mix - Triguero-Ruiz, Francisco Andrés; Ávila-Cano, Antonio Jesús; Trujillo-Aranda, Francisco (Elsevier, 2023)
In this paper we explore the concept of concentration/diversification of energy sources. Concentration is identified by a number that represents the energy mix, i.e., the vector of the share quota of each energy source in total consumptions. We construct a new concentration index which is a mathematical distance and economically interpretable and apply it to the world's major economies for the period between 1965 and 2018. We find that the diversification process has been considerable, intense, and widespread, and has presented different territorial patterns.
Keywords: Energía -- Consumo; Desarrollo energético; Recursos energéticos; Industria petroquímica; Concentration; Energy mix; Energy diversification index